Effect of Light Therapy on Reducing Depressive Symptoms in Seasonal Affective Disorder Sufferers - Riniati, Wa Ode; Supriyanti, Supriyanti; Guilin, Xie; Jiao, Deng; Anripa, Nuralfin (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Seasonal Affective Disorder (SAD) is a mental disorder related to seasonal changes that occur during winter due to lack of exposure to sunlight. Light therapy has become a focus in treating depressive symptoms in sufferers of Seasonal Affective Disorder. However, more in-depth research is still needed to clarify the effect of light therapy in reducing symptoms of depression in sufferers of Seasonal Affective Disorder. This study aims to explore the effect of light therapy on reducing depressive symptoms in sufferers of Seasonal Affective Disorder and to provide scientific evidence that can support the use of light therapy as an effective treatment method. This research method uses a randomized controlled clinical study design involving adult participants who have been diagnosed with Seasonal Affective Disorder. Participants were divided into two groups, one group received light therapy for a certain period of time, while the control group received usual treatment. Depressive symptoms were evaluated before, during, and after the intervention using proven rating scales. The results showed that participants who received light therapy experienced a significant reduction in depressive symptoms compared to the control group. Light therapy has consistently been shown to improve mood and energy and reduce symptoms of depression in people with Seasonal Affective Disorder. The conclusion of this study shows that light therapy has a positive influence in reducing symptoms of depression in sufferers of Seasonal Affective Disorder. The use of light therapy as a non-pharmacological intervention can be an effective and relatively safe therapeutic option to reduce the impact of Seasonal Affective Disorder on an individual's well-being. Thus, light therapy can be integrated as part of the treatment for sufferers of Seasonal Affective Disorder.